Óxidos a base de Ca(Zr,Sn)O3 aplicados na fotodegradação dos corantes remazol vermelho 133% e remazol amarelo ouro - Guimarães, Cynthia Ribeiro (2019)
Perovskites are crystalline structures that present general formula ABO3, having the cubic structure as the ideal, being possible present geometric variations according to some parameters. These oxides are structures reported in the literature because of their distinct chemical and physical properties, providing a range of technological applications. Among its applications, highlight electronic, magnetic, refractory materials and as catalysts in photocatalytic processes. The present work aims to evaluate the substitution of the Zr^4+ by Sn^4+ cation in the oxides CaZrxSn1-xO3 (x = 0,00; 0,25; 0,50; 0,75 and 1,00) obtained by the polymer precursors method, as well as how to evaluate the influence of calcium precursor salt in obtaining these oxides. The influence of the system aiming to optimize the photocatalytic properties of these materials for the discoloration of Remazol Yellow Gold (RNL) and Remazol Red 133% (RV) was evaluated. The oxides were obtained by the polymeric precursor method at 700 ° C and were characterized by X-ray Diffraction (XRD), Infrared (IR) Absorption Spectroscopy, Raman and UV Absorption Spectroscopy Visible (UV-Vis). The XRD results showed that the oxides have an orthorhombic perovskite structure, with the space group Pbnm in CaSnO3 and Pnma for CaZrO3 with distortions caused by substitution at site B, for both systems starting from the different salts. Since the replacement of a 0,69 Å (Sn^4+) ionic cation with a 0,79 Å (Zr^4+) ionic cation occurs, distortions in the octaedral are caused by simultaneous competition of the B cations at the octahedron sites of the structures. Regarding the influence of calcium precursor salts on sample preparation, there is a change in the unit cell volume, width at half height reflecting the size of the crystallite. Higher values of unit cell volume and crystallite size were observed for the system synthetized using calcium nitrate salt. Samples with higher Sn4+ percentage showed higher calcium carbonate formation and changes in spectra profiles with the replacement of B cations in the system. UV-Vis spectral are present showed an increase in Egap with cation substitution, with different results regarding the variation of composition in relation to the type of starting precursor salt, and the system with the calcium acetate precursor salt Egap direct from 3,28 to 5,02 eV and indirect Egap 4,1 to 5,63 eV; and band gap values between 3,4 to 5,6 eV - direct gap; and 3,79 to 5,8 eV for the indirect gap for samples obtained from calcium nitrate precursor salt. Regarding the process of discoloration of dyes, the materials showed promising results, with 25 mg of oxides under UV-C radiation for 6 hours, and CaSnO3 from the precursor calcium acetate salt showed the best efficiency for RV (75,7%) in 6 hours and for the RNL CaZr0,25Sn0,75O3 starting from the most effective calcium nitrate precursor salt (65,2%) in 6 hours. Thus, cation replacement at octahedron sites and salt variation in synthesis may favor photocatalytic properties of materials.